Long-Term Financial Forecasting as a Part af Strategic Planning in Local Government Units - Adamowicz, Mieczysław (Olsztyn Economic Journal, 2018)
The aim of this paper is to present, on the example of Karczew municipality, long term financial forecasting as a component of strategic planning and to evaluate it as a tool for managing the socio-economic development in a local self-government unit. The paper has two main parts. In the first part, a theoretical background for strategic and financial management and forecasting is presented and in the second part, a case study of financial forecasting for the Karczew municipality is described. The main conclusion of the paper is that financial forecasting and strategic planning are important tools for the management of the municipal units if these are linked within local present budgeting and are implemented in an integrated way. Analysis of the municipality of Karczew shows that the current integrated strategies create a useful foundation for the effective functioning of the municipal unit.